Trends in mitochondrial unfolded protein response research from 2004 to 2022: A bibliometric analysis - Ye, Zelin; Chai, Ruoning; Luan, Yujie; Du, Yihang; Xue, Wenjing; Shi, Shuqing; Wu, Huaqin; Wei, Yi; Zhang, Limei; Hu, Yuanhui (Frontiers in Cell and Developmental Biology, 2023)
The mitochondrial unfolded protein response (UPRmt) is a stress response pathway that regulates the expression of mitochondrial chaperones, proteases, and other proteins involved in protein folding and degradation, thereby ensuring proper mitochondrial function. In addition to this critical function, the UPRmt also plays a role in other cellular processes such as mitochondrial biogenesis, energy metabolism, and cellular signaling. Moreover, the UPRmt is strongly associated with various diseases. From 2004 to 2022, there has been a lot of interest in UPRmt. The present study aims to utilized bibliometric tools to assess the genesis, current areas of focus, and research trends pertaining to UPRmt, thereby highlighting avenues for future research. There were 442 papers discovered to be related to UPRmt, with the overall number of publications rising yearly. International Journal of Molecular Sciences was the most prominent journal in this field. 2421 authors from 1402 institutions in 184 nations published studies on UPRmt. The United States was the most productive country (197 documents). The top three authors were Johan Auwerx, Cole M Haynes, and Dongryeol Ryu. The early focus of UPRmt is “protein”. And then the UPRmt research shifted from C. elegans back to mammals, and its close link to aging and various diseases. The top emerging research hotspots are neurodegenerative diseases and metabolic diseases. These findings provide the trends and frontiers in the field of UPRmt, and valuable information for clinicians and scientists to identify new perspectives with potential collaborators and cooperative countries.